Neonatal Abstinence Syndrome: Presentation and Treatment Considerations. Issue 4 (July 2016) - Jones, Hendrée E.; Kaltenbach, Karol; Johnson, Elisabeth; Seashore, Carl; Freeman, Emily; Malloy, Erin
Abstract : Abstract: This clinical case conference discusses the treatment of a pregnant woman with opioid use disorder in a comprehensive care program that includes buprenorphine pharmacotherapy. The presentation summarizes common experiences that pregnant women who receive buprenorphine pharmacotherapy face, and also what their prenatally opioid-exposed children confront in the immediate postpartum period. It describes the elements of a successful comprehensive care model and corollary neonatal abstinence syndrome treatment regimen. Expert commentary is included on issues that arise in the buprenorphine induction and maintenance throughout the prenatal and postpartum periods and in the treatment of co-occurring mental health problems during both the prenatal and postpartum periods, particularly the treatment of depression. There is also expert commentary on the care of opioid-exposed neonates, with attention to the treatment for neonatal abstinence syndrome.